Analisis Pemberian Kredit Pada Program Kemitraan) PT. Telkom (Studi Pada Usaha Mikro Kecil dan Menengah (UMKM) Sektor Industri Binaan PT. Telkom Malang Regional V Jawa Timur - Intan Nuraini; Juni Herawati (Jurnal Ilmiah Mahasiswa FEB, 2014)
Since 2010,  the growth rate of  SMEs  are increase significantly so it  can decrease  unemployment and is able to  improve the Indonesian economy. However,  there are some problems of  SMEs  there are  capital, resources, promotion and raw materials. To respond to these problems, the government established the Corporate Social Responsibility (CSR) which is conducted by the State Owned Enterprises (SOEs), and it call  as Partnership Program and Community Development  that provide credit and assistance to SMEs in developing their business. This study aimed to examine the differences before and after crediting Partnership Program PT. Telkom Malang and sales turnover for the development of SMEs. Business development here projected  by  profitability of SMEs. The population was assisted partner SMEs PT. Telkom Malang in 2010-2013. Sampling technique  is  purposive sampling and obtained 7 SMEs  for  research samples. The analysis technique used is t test average difference and calculate the average profitability ratios such as the ratio of net profit margin (NPM) and Return On Investment (ROI). Confidence level (α) used in this study was 0.05. The results using the t test average difference indicates that there is a difference before and after the provision of credit and an increase in profitability of SMEs. The increase in this ratio indicate that lending Partnership effect on the development of SMEs.Keywords:   Corporate Social Responsibilty, Partnership Program and Community Development,  PT. Telekomunikasi Indonesia Tbk., Credit, Sales turnover, profitability, business development,  Micro, Small and Medium Enterprises (SMEs).